Association of LTF, ENAM, and AMELX polymorphisms with dental caries susceptibility: a meta-analysis - Roohollah Sharifi; Sajjad Jahedi; Hamid Reza Mozaffari; Mohammad Moslem Imani; Masoud Sadeghi; Amin Golshah; Hedaiat Moradpoor; Mohsen Safaei (BMC, 2020)
Abstract Background This meta-analysis evaluated the association of LTF, ENAM, and AMELX polymorphisms with dental caries susceptibility. Methods We searched the Scopus, PubMed/Medline, Web of Science, and Cochrane Library databases to retrieve articles published by October 2019. Review Manager 5.3 software was used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs). The results of publication bias tests were retrieved by Comprehensive Meta-Analysis 2.0 software. Results A total of 150 relevant records were identified; out of which, 16 were entered into the analysis (4 studies assessed LTF, 11 ENAM, and 11 AMELX polymorphisms). Of all polymorphisms, there was a significant association only between ENAM rs3796704 polymorphism and dental caries susceptibility. Both ENAM rs3796704 and AMELX rs17878486 polymorphisms had a significant association with dental caries risk in the Caucasian ethnicity and the studies including caries-free control group. Conclusions The results of this meta-analysis showed that the G allele and the GG genotype of ENAM rs3796704 were associated with an increased risk of caries in the case group compared with the control group. But there was no association between LTF rs1126478, ENAM (rs1264848 and rs3796703), and AMELX (rs946252, rs17878486, and rs2106416) polymorphisms and dental caries susceptibility.